Determinan Pendapatan Usaha Tani Padi Sawah di Kabupaten Sintang - Rosita Maharani; Josua Parulian Hutajulu; Rakhmad Hidayat (Universitas Galuh, 2026)
Rice farming is the main source of rice supply, but it still faces the obstacle of low production, which affects farming income. The purpose of this study is to examine the amount of farming income and the factors that affect rice farming income in Gemba Raya Village, Kelam Permai Subdistrict, Sintang Regency. The research was conducted from August 2025 to January 2026 with a sample of 72 rice farmers determined using proportionate stratified random sampling. Income analysis used farm income calculations, while factors affecting income were analyzed using the Cobb-Douglas Unit Output Price profit function. The results of this study show that the average annual income of farmers is Rp. 10,041,131. The analysis of factors affecting income shows that land area, labor wages, and the use of high-quality seeds have a positive and significant effect on rice farming income. The price of NPK fertilizer has a negative and significant effect, while the price of urea fertilizer has no significant effect on income. The price of herbicides has a positive and significant effect on the first planting season. This study concludes that an increase in rice farming income can be achieved through the optimization of land area, the efficient use of labor, and the use of high-quality seeds.